2017
DOI: 10.1021/acs.energyfuels.7b01663
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Applicability Analysis of CO2-ECBM Technology Based on CO2–H2O–Coal Interactions

Abstract: In view of the failed field testing of CO2-ECBM technology, the feasibility and applicability of the CO2-ECBM process were analyzed based on interactions among CO2, H2O, and minerals in the coal reservoir by conducting flooding experiments of coal samples using nuclear magnetic resonance (NMR) technology. CO2 can change the wettability of the coal surface, and adsorbed water can be changed into free water. CO2 is adsorbed constantly on the coal surface, leading to the swelling of the coal matrix. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Storing carbon dioxide (CO 2 ) into unmineable coal seams and simultaneously recovering CH 4 (CO 2 -ECBM) has become a feasible way to mitigate CO 2 emissions. As an alternative option to CO 2 -ECBM, a novel technical proposal, that is, directly injecting oxygen-enriched coal-combustion flue gas into coal seams, has been gaining broad interest. , This technology is expected to cut the cost regarding denitration (DeNO x ) and flue gas desulfuration. Next, the multiple interactions between NO x , SO 2 , and coal matrix are expected to stably store oxygen-enriched coal-combustion flue gas within coal reservoirs in the geologic time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Storing carbon dioxide (CO 2 ) into unmineable coal seams and simultaneously recovering CH 4 (CO 2 -ECBM) has become a feasible way to mitigate CO 2 emissions. As an alternative option to CO 2 -ECBM, a novel technical proposal, that is, directly injecting oxygen-enriched coal-combustion flue gas into coal seams, has been gaining broad interest. , This technology is expected to cut the cost regarding denitration (DeNO x ) and flue gas desulfuration. Next, the multiple interactions between NO x , SO 2 , and coal matrix are expected to stably store oxygen-enriched coal-combustion flue gas within coal reservoirs in the geologic time scale.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption capacity of coal to carbon dioxide (CO 2 ) is greater than that of CH 4 , and the adsorbed CH 4 in micropores can be replaced by CO 2 by competitive adsorption, which positively affects CBM recovery. , The very first CO 2 -enhanced CBM (CO 2 -ECBM) studies were conducted by American researchers. The field application of CO 2 -ECBM (Figure ) has demonstrated that CO 2 injection can increase CBM production and that CO 2 can be geologically sequestrated. Wang et al conducted numerical simulations and demonstrated that, in general, the permeability evolution of reservoirs has a downward trend.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 displacement can be adopted for CBM recovery [9]. CO 2 -enhanced coalbed methane (CO 2 -ECBM) technology involves the injection of CO 2 into a coal seam rich in CBM, to sequester CH 4 , promotes clean green energy, and is widely used in the production of deep ultra-low permeability coal seams [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%